The formulated microbicide RC-101 was safe and antivirally active following intravaginal application in pigtailed macaques. - Alexander M Cole; Dorothy L Patton; Lisa C Rohan; Amy L Cole; Yvonne Cosgrove-Sweeney; Nicole A Rogers; Deena Ratner; Alexandra B Sassi; Carol Lackman-Smith; Patrick Tarwater; Bharat Ramratnam; Piotr Ruchala; et al. (PLoS ONE)
Background RC-101 is a congener of the antiretroviral peptide retrocyclin, which we and others have reported is active against clinical HIV-1 isolates from all major clades, does not hemagglutinate, and is non-toxic and non-inflammatory in cervicovaginal cell culture. Herein, film-formulated RC-101 was assessed for its antiviral activity in vitro, safety in vivo, retention in the cervix and vagina, and ability to remain active against HIV-1 and SHIV after intravaginal application in macaques. Methodology/principal findings RC-101 was formulated as a quick-dissolving film (2000 µg/film), retained complete activity in vitro as compared to unformulated peptide, and was applied intravaginally in six pigtailed macaques daily for four days. At one and four days following the final application, the presence of RC-101 was assessed in peripheral blood, cervicovaginal lavage, cytobrushed cervicovaginal cells, and biopsied cervical and vaginal tissues by quantitative western blots. One day following the last film application, cervical biopsies from RC-101-exposed and placebo-controlled macaques were collected and were subjected to challenge with RT-SHIV in an ex vivo organ culture model. RC-101 peptide was detected primarily in the cytobrush and biopsied cervical and vaginal tissues, with little to no peptide detected in lavage samples, suggesting that the peptide was associated with the cervicovaginal epithelia. RC-101 remained in the tissues and cytobrush samples up to four days post-application, yet was not detected in any sera or plasma samples. RC-101, extracted from cytobrushes obtained one day post-application, remained active against HIV-1 BaL. Importantly, cervical biopsies from RC-101-treated animals reduced RT-SHIV replication in ex vivo organ culture as compared to placebo-treated animals. Conclusions/significance Formulated RC-101 was stable in vivo and was retained in the mucosa. The presence of antivirally active RC-101 after five days in vivo suggests that RC-101 would be an important molecule to develop further as a topical microbicide to prevent HIV-1 transmission.